2022
DOI: 10.1007/s40894-022-00181-w
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with Children and Adolescents: A Systematic Review of Participatory Methods and Approaches in Research Informing the Development of Health Resources and Interventions

Abstract: In research, participatory approaches involve engaging in the research with people and empower co-researchers to have a voice. The aim of this review was to synthesize the methods and approaches used to enable children, adolescents, and families to be involved in a participatory approach in research conducted to inform development of health resources and interventions aimed at children and adolescents. Key databases were searched systematically using key word and subject heading searches and included studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The WHO–UNICEF–Lancet Commission calls for young people to be involved in creating policy that concerns them and their health [ 3 , 4 ]. Efforts to involve young people in policy and decision-making and in research are currently hampered by a lack of awareness of methods for engaging them effectively [ 78 ]. This review suggests that genuinely deliberative methods involving dialogue and mutual respect between young people, parents and professionals which go further than consultation not only achieve consensus on priorities for action but are also the most satisfying and beneficial for participants.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO–UNICEF–Lancet Commission calls for young people to be involved in creating policy that concerns them and their health [ 3 , 4 ]. Efforts to involve young people in policy and decision-making and in research are currently hampered by a lack of awareness of methods for engaging them effectively [ 78 ]. This review suggests that genuinely deliberative methods involving dialogue and mutual respect between young people, parents and professionals which go further than consultation not only achieve consensus on priorities for action but are also the most satisfying and beneficial for participants.…”
Section: Discussionmentioning
confidence: 99%
“…These can be achieved through participation in relevant activities related to building internal capacity, including health and well‐being 13 . Co‐design uses a variety of activities to appeal to different participants and generate engagement 17 . The variety of activities and learning mechanisms in our co‐design workshops provided a range of opportunities for the AWG to meet those learning outcomes 13 .…”
Section: Discussionmentioning
confidence: 99%
“…13 Co-design uses a variety of activities to appeal to different participants and generate engagement. 17 The variety of activities and learning mechanisms in our co-design workshops provided a range of opportunities for the AWG to meet those learning outcomes. 13 Our results showed that the AWG's teamwork, communication and leadership skills were developed, and choosing interactive presentations as a delivery mechanism enhanced their self-efficacy, resilience, and emotional regulation skills.…”
Section: Discussionmentioning
confidence: 99%
“…A user-centred approach can provide a solution for developing resources that are culturally sensitive, relevant and age appropriate while making use of research in the field from other contexts (Brooks et al, 2019(Brooks et al, , 2021Crosby et al, 2020;Nsangi et al, 2020). The available literature does not contain reference to any standardised framework; one systematic review of participatory research with children and adolescents identified an imbalance of participation towards the earlier stages in which information gathering is the focus, opposed to during later stages of development (Freire et al, 2022). Brooks et al (2019) describe the methodology for development of a culturally appropriate toolkit promoting mental health literacy in Indonesia.…”
Section: User-centred Design Of School Resourcesmentioning
confidence: 99%